The Implementation of Democracy in The Middle of The Application of Ite Law - Hermawan, Ian Aji (Wacana Hukum, 2022)
Democracy in Indonesia has been running for quite a long time since Indonesia was founded until now, which is approximately 76 years. each order has its own characteristics in carrying out democracy in Indonesia according to the conditions and political interests at that time.So that each ruler has his own interpretation of democracy in the Sukarno era, in the guided democracy during the Suharto era, there was Pancasila democracy and in the reformation period, Pancasila democracy was implemented in accordance with the constitution. there is little difference in implementing Pancasila democracy during the New Order era and during the reformation period.This difference can be seen where during the new code of democracy Pancasila was implemented but not wholeheartedly because the authorities at that time implemented a subversion law, while during this reformation period, especially in the last 10 years, the government implemented a democratic system but also implemented a law on information and electronic transactions. considered by some legal and political observers to be a substitute for subversive laws.